Hemoglobin-Based Oxygen Carriers: Potential Applications in Solid Organ Preservation - Cao, Min; Wang, Guoqing; He, Hongli; Yue, Ruiming; Zhao, Yong; Pan, Lingai; Huang, Weiwei; Guo, Yang; Yin, Tao; Ma, Lina; Zhang, Dingding; Huang, Xiaobo (Frontiers in Pharmacology, 2021)
Ameliorating graft injury induced by ischemia and hypoxia, expanding the donor pool, and improving graft quality and recipient prognosis are still the goals pursued by the transplant community. The preservation of organs during this process from donor to recipient is critical to the prognosis of both the graft and the recipient. At present, static cold storage, which is most widely used in clinical practice, not only reduces cell metabolism and oxygen demand through low temperature but also prevents cell edema and resists apoptosis through the application of traditional preservation solutions, but these do not improve hypoxia and increase oxygenation of the donor organ. In recent years, improving the ischemia and hypoxia of grafts during preservation and repairing the quality of marginal donor organs have been of great concern. Hemoglobin based oxygen carriers (HBOCs) are "made of" natural hemoglobins that were originally developed as blood substitutes but have been extended to a variety of hypoxic clinical situations due to their ability to release oxygen. Compared with traditional preservation protocols, the addition of HBOC to traditional preservation protocols provide more oxygen to organs to meet their energy metabolic needs, prolong preservation time, reduce ischemia/reperfusion injury to grafts, improve graft quality, and even increase the number of transplantable donors. The focus of the present study was to review the potential applications of HBOCs in solid organ preservation and provide new approaches to understanding the mechanism of the promising strategies for organ preservation.